Perlindungan Hukum bagi Direksi atas Tagihan Pajak yang Masih Terutang Pasca Pemberesan Harta Pailit - Ketut Octania Fineta Diarsa; Etik Yuniati; Surahmat; Tofani Yurisar Akbar (Notaire, 2023)
AbstractThe provisions of Article 2 paragraph (6) and Article 32 paragraph (2) of Law Number 6 of 1983 concerning General Provisions and Tax Procedures as last amended by Government Regulation in Lieu of Law Number 2 of 2022 concerning Job Creation (UU KUP) resulted in the Directors of a Limited Liability Company having been terminated bankruptcy can be held personally responsible for tax debt bills that are still outstanding after the settlement of bankruptcy assets. As with the principle of the Business Judgement Rule, directors who run a company with the principles of Good Corporate Governance will avoid being held personally liable when a Limited Liability Company is declared bankrupt. However, the Directorate General of Taxes continues to submit tax debt claims to the directors personally because the bankruptcy assets of the Limited Liability Company are not sufficient to pay off the tax debt. Meanwhile, the tax debt continues to arise because the NPWP of the Limited Liability Company after the settlement is still active. The NPWP which is still active causes the dissolution of a Limited Liability Company that is no longer in operation to be invalid because there is an accrued tax debt that must be paid. This research is normative legal research using statutory, conceptual, and case approaches. This research is expected to provide answers to legal protection and certainty for directors and for Limited Liability Companies which will be dissolved after the process of settling bankruptcy assets is completed by the curator.Keywords: Bankruptcy; Tax Debt; Business Judgement Rule. AbstrakKetentuan Pasal 2 ayat (6) dan Pasal 32 ayat (2) Undang-Undang Nomor 6 Tahun 1983 tentang Ketentuan Umum dan Tata Cara Perpajakan sebagaimana diubah terakhir dengan Peraturan Pemerintah Pengganti Undang-Undang Nomor 2 Tahun 2022 tentang Cipta Kerja (UU KUP) mengakibatkan Direksi Perseroan Terbatas yang telah diputus pailit dapat diminta pertanggungjawaban secara pribadi atas tagihan utang pajak yang masih terutang pasca pemberesan harta pailit. Sebagaimana prinsip Business Judgement Rule maka direksi yang menjalankan perusahaan dengan kaidah Good Corporate Governance akan terhindar dari pertanggungjawaban secara pribadi ketika Perseroan Terbatas diputus pailit. Akan tetapi Direktorat Jenderal Pajak tetap mengajukan tagihan utang pajak ke pribadi direksi karena harta pailit dari Perseroan Terbatas tidak cukup untuk melunasi utang pajak. Sementara itu, utang pajak tetap timbul karena NPWP Perseroan Terbatas pasca dilakukan pemberesan masih dalam keadaan aktif. NPWP yang masih aktif tersebut mengakibatkan pembubaran Perseroan Terbatas yang sudah tidak beroperasi menjadi tidak dapat dilakukan karena terdapat utang pajak yang masih harus dibayar. Penelitian ini merupakan penelitian hukum normatif dengan menggunakan pendekatan perundang-undangan, konseptual, dan kasus. Penelitian ini diharapkan dapat memberikan jawaban atas perlindungan dan kepastian hukum bagi direksi dan bagi Perseroan Terbatas yang akan dibubarkan setelah proses pemberesan harta pailit selesai dilakukan oleh kurator. Kata Kunci: Pailit; Utang Pajak; Business Judgement Rule.